Estudo de artrodese lombar minimamente invasiva lateral transpsoas: análise de parâmetros radiológicos, afundamento do espaçador intersomático e suas correspondências clínicas - Marchi, Luis Henrique Larcher [UNIFESP] (2016)
To investigate the event of sinking of the intersomatic spacer in lumbar fusion procedures by the XLIF method without the use of transpedicular screw supplementation. Methods: In the investigation of time of onset, clinical significance and protective factors, we used a retrospective analysis of a first cohort: 74 cases treated with XLIF. The cases were divided into two groups according to the spacer that was used 18mm and 22mm. Radiological and clinical parameters were evaluated up to one year postoperatively. In lateral radiographs we used a gradation of sinking of the spacer (degree 0-III). In a second cohort, we investigated risk factors and selected cases with low predisposition to sink. We used a case-control study with 86 cases divided by the outcomes: sinking grade II / III or grade 0 / I. Demographic, pathological and surgical data were analyzed. A score of factors correlated with sinking was tested. Results: In the first study, we found that sags of more advanced degrees were found in the 18mm group (p = 0.01). The event was detected at the point six weeks after surgery and did not progress significantly. The occurrence of more advanced degrees was correlated with transient low back pain at the six-week point. At the last point of analysis, we observed that in the 22mm group, 14% of the cases had grade II / III dip as opposed to 30% in the 18mm group. In the second study, the following risk factors were correlated with sinking group II / III: spondylolisthesis (92% vs 21%, p <0.001); Scoliosis (33% vs 12%, p = 0.033); Female (75% vs 42%, p = 0.007); Age (57.3 vs 67.7, p <0.001). These factors were used in a score (from 0-4) to assess the risk of each case. Scores ?2 were predictors of sinking with 92% sensitivity and 72% specificity. Conclusions: The occurrence of sinking is precocious, it should be carefully evaluated at the beginning of the follow-up because it reflects clinically and in loss of surgical correction. The use of wider spacers may decrease the occurrence. In addition, in the selection of eligible cases using predictive sinking factors found the probability of favorable evolution is 98%.